RETRACTED: Exploring Groundwater Quality Assessment: A Geostatistical and Integrated Water Quality Indices Perspective (Water, (2023), 16, 1, (138), 10.3390/w16010138) - Masood M.U.; Rashid M.; Haider S.; Naz I.; Pande C.B.; Heddam S.; Alshehri F.; Elkhrachy I.; Ahsan A.; Sammen S.S. (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
The Water Editorial Office retracts the article ?Exploring Groundwater Quality Assessment: A Geostatistical and Integrated Water Quality Indices Perspective? [1], cited above. Following publication, concerns were brought to the attention of the Editorial Office regarding an overlap between this article [1] and a previously published article [2] originating from a different authorship group. Adhering to our complaint?s procedure, an investigation was conducted by the Editorial Office and Editorial Board that confirmed a significant overlap, which included Figures 2, 5, 7, 8, 9, 11, 12, 13, 14, 15 and 16 and Tables 2, 4, 5, 6, 7, 8 and 9, without appropriate citations. As a result, the Editorial Office, Editorial Board, Guest Editor and authors have decided to retract this article [1] as per MDPI?s retraction policy (https://www.mdpi.com/ethics#_bookmark30, accessed on 13 April 2024) and in line with the Committee on Publication Ethics retraction guidelines (https://publicationethics.org/retraction-guidelines, 13 April 2024). This retraction was approved by the Editor-in-Chief of the journal Water. The authors agree to this retraction. ? 2024 by the authors.